Practice of exclusive breastfeeding and nutritional status of infants aged 6 months - Reflina Grace Temomona; Luluk Yuliati (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2023)
Malnutrition in infants can occur when babies do not get enough nutrition or do not get the balanced nutrition needed for healthy growth and development. Exclusive breastfeeding has an important role in preventing malnutrition in infants. This study was conducted to determine the relationship between exclusive breastfeeding and the nutritional status of infants aged 6 months.This research is an observational analytic research by applying the approach cross sectional, the population used was all infants aged 6 months in the Work Area of the Lelilef Health Center, with a total sample of 30 respondents selected based on purposive sampling technique. The results of the research data were analyzed using nonparametric analysis with Fisher's Exact Test. The results showed that almost all mothers (83,3%) gave exclusive breastfeeding, and almost all babies had normal nutritional status (83,3%). This study shows that there is a relationship between exclusive breastfeeding and the nutritional status of infants aged 6 months with value p=0,022. This good practice in exclusive breastfeeding can be achieved with the mother's persistence in breastfeeding and full support from the family and health workers.